Efforts to Increase Islamic Spirituality in Pondok Parsulukan - Dalimunthe, Irwan Saleh; Zulhamri, Zulhamri (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
The coaching of worship (spiritual) for the elderly at the Al-Yusufiyah Foundation aims to increase awareness and motivation in carrying out worship, strengthen faith, moral responsibility, and personality development, as well as deepen piety to God Almighty. This research is a qualitative descriptive study that explores the development of worship in the elderly. The research subjects included the elderly and nursing home managers. Data collection methods include interviews, observations, and documentation. This research was carried out for three months with a step-by-step process. The results of the study show that the implementation of worship coaching through congregational prayers, the study of taklim councils, suluk, tawajjuh, and the study of the Qur'an provide significant benefits for the daily lives of the elderly. The coaching method involves the study of taklim councils, suluk, tawajjuh, and the study of the Qur'an with materials of faith, worship, and dhikr. The obstacles faced by nursing home administrators are the lack of discipline of the elderly in attending coaching activities due to health reasons.